Settlement Network Development Policy in Hungary in the Period of State Socialism (1949-1985) - Hajdú, Zoltán (Discussion Papers, 1993)
Hungarian historical development can not only be divided into distinct political-historical eras, related sectoral policies have also experienced a continuous transformation during the different eras. The volume gives an overview of the specific features and provides an analysis of settlement and settlement network development policies of the era of state socialism (1949- 1985). The development of towns was given specific emphasis according to the prevailing ideological-political system of values of the era. The demand for forming network connections within the settlement network did arise, however, it soon became obvious that despite the monopoly of power of the state, it failed to achieve the alignment of processes to pre-established plans.